Out-of-pile experiments for design validation of material irradiation test loop. (May 2022) - Avinash, Ch.S.S.S.; Singh, Kulbir; Rao, E. Hemanth; Malarvizhi, B.; Das, Sanjay Kumar; Kumar, R. Suresh; Lydia, G.; Ponraju, D.; Nashine, B.K.; Athmalingam, S.; Venkatraman, B.
Highlights: U-tube annular heat exchanger with an oscillating sodium column has been designed for carrying out material irradiation tests. Thermal performance of the oscillating liquid sodium heat exchanger is determined in out of pile experiments at various load conditions. Nitrogen gas is circulated through the annulus surrounding the U-tube column for heat removal. Nitrogen gas flow required for maintaining a desired steady state temperature in the specimen chamber at various heat loads ranging from 0.5 kW to 2 kW is found out experimentally. Performance of the heat transfer loop found to be satisfactory in out of the pile experiments. Abstract: An innovative sodium loop has been conceptualised for irradiation of material specimens in sodium at high temperature, in Fast Breeder Test Reactor (FBTR). The loop consists of a specimen chamber and an oscillating sodium column heat exchanger to maintain the test specimen at required temperature during the irradiation campaign. To validate the design, a full-scale out-of-pile test loop with sodium system and auxiliary circuits, was setup at IGCAR. Irradiation heat was simulated by cartridge heater mounted at the specimen chamber. Oscillating sodium column working in tandem with a cooling gas recirculation system was employed for heat removal. Experiments were conducted at different heat loadings up to 2 kW and specimen chamber temperatures from 300 °C to 500 °C were achieved successfully, giving a satisfactory feedback for the design of proposed in-pile loop in FBTR.